Pheromonal and Behavioral Cues Trigger Male-to-Female Aggression in Drosophila. - Fernandez, M.P.; Chan, Y.B.; Yew, J.Y.; Billeter, J.C.; Dreisewerd, K.; Levine, J.D.; Kravitz, E.A. (PLoS Biology, 2010)
Appropriate displays of aggression rely on the ability to recognize potential competitors. As in most species, Drosophila males fight with other males and do not attack females. In insects, sex recognition is strongly dependent on chemosensory communication, mediated by cuticular hydrocarbons acting as pheromones. While the roles of chemical and other sensory cues in stimulating male to female courtship have been well characterized in Drosophila, the signals that elicit aggression remain unclear. Here we show that when female pheromones or behavior are masculinized, males recognize females as competitors and switch from courtship to aggression. To masculinize female pheromones, a transgene carrying dsRNA for the sex determination factor transformer (traIR) was targeted to the pheromone producing cells, the oenocytes. Shortly after copulation males attacked these females, indicating that pheromonal cues can override other sensory cues. Surprisingly, masculinization of female behavior by targeting traIR to the nervous system in an otherwise normal female also was sufficient to trigger male aggression. Simultaneous masculinization of both pheromones and behavior induced a complete switch in the normal male response to a female. Control males now fought rather than copulated with these females. In a reciprocal experiment, feminization of the oenocytes and nervous system in males by expression of transformer (traF) elicited high levels of courtship and little or no aggression from control males. Finally, when confronted with flies devoid of pheromones, control males attacked male but not female opponents, suggesting that aggression is not a default behavior in the absence of pheromonal cues. Thus, our results show that masculinization of either pheromones or behavior in females is sufficient to trigger male-to-female aggression. Moreover, by manipulating both the pheromonal profile and the fighting patterns displayed by the opponent, male behavioral responses towards males and females can be completely reversed. Therefore, both pheromonal and behavioral cues are used by Drosophila males in recognizing a conspecific as a competitor.